A compact dual‐polarized antenna using slotted patch with broad beam width. Issue 12 (3rd September 2020) - Shi, Junhao; Zhai, Huiqing; Zeng, Yi
Abstract: In this article, a broadband dual‐polarized microstrip antenna with low profile and compact horizontal size is presented. By using the grid‐slotted patch, dual modes can be excited to broaden the operating bandwidth of the proposed antenna. A broad bandwidth of 25%(1.4‐1.8 GHz) for return loss >10 dB is achieved in our design. Two orthogonal linear polarization waves are excited when two pairs of aperture are utilized to couple the grid‐slotted patch. Current distribution varies with frequency which results in a broad and varying beam width. Consequently, a roughly flat gain curve appears in our design. The proposed antenna achieves a low profile of 0.09 λ0 (λ0 is the free‐space wavelength at 1.6 GHz) and a compact horizontal size. A prototype is fabricated and measured to prove the simulation.